Endotracheal intubation with barrier protection. Issue 7 (1st June 2020) - Jazuli, Farah; Bilic, Monika; Hanel, Erich; Ha, Michael; Hassall, Kelly; Trotter, Brendon Gordon
Abstract : Given the high risk of healthcare worker (HCW) infection with COVID-19 during aerosol-generating medical procedures, the use of a box barrier during intubation for protection of HCWs has been examined. Previous simulation work has demonstrated its efficacy in protecting HCWs from cough-expelled droplets. Our objective was to assess its ability to protect HCWs against aerosols generated during aerosol-generating medical procedures. We used a battery-powered vapouriser to assess movement of vapour with: (1) no barrier; (2) a box barrier; and (3) a box barrier and a plastic sheet covering the box and patient's body. We visualised the trajectory of vapour and saw that the vapour remained within the barrier space when the box barrier and plastic sheet were used. This is in contrast to the box barrier alone, where vapour diffused towards the feet of the patient and throughout the room, and to no barrier where the vapour immediately diffused to the laryngoscopist. This demonstrates that the box with the plastic sheet has the potential to limit the spread of aerosols towards the laryngoscopist, and thus may play a role in protecting HCWs during aerosol-generating medical procedures. This is of particular importance in the care of patients with suspected COVID-19.